(untitled) (Research, Society and Development, 2022)
The inclusion of partially or totally visually impaired students is a reality in the Brazilian educational process. This issue gained momentum in Brazil and around the world around 1990 and is a relevant issue in discussions and debates on inclusive education. Education is fundamental for man to guarantee his existence based on natural changes. She is responsible for developing the production of knowledge and culture. From the identification of cultural elements and also the discovery of new ways to facilitate the assimilation of these elements, Education becomes a requirement. With regard to people with disabilities, Education is a fundamental issue in the world and has been the object of countless debates and reflections. Including the visually impaired person in basic education deserves a closer look, due to the possible rejection of the group towards this person, and thus, we cannot work an inclusion where we only place this person among others, and let their interaction flow naturally . Consistent and responsible work is needed for inclusion to happen effectively. Therefore, they propose to analyze specific issues related to this group, in order to ensure greater effectiveness in this inclusion, or interaction. We must guarantee equity for all, because in this way we will have a fair and true education, meeting the wishes of all individuals involved in the teaching-learning process. In the article, we present reflections on the theme from the historical-socio-cultural context of blindness, the current legislation in Brazil and some aspects of the inclusive process of the visually impaired in University Education. Therefore, a literary review of the studies presented in specialized journals, periodicals and academic papers on the subject and its aspects relevant to society was carried out, as well as in databases such as Pubmed, Scielo, Google Scholar, virtual libraries, among others.